Glycols – Method for the determination of diethylene glycol, ethylene glycol and propylene glycol in workplace air using gas chromatography [Air Monitoring Methods, 2018]. Issue 3 (26th July 2018) - Giesen, Y.; Friedrich, C.; Breuer, D.; Fauss, J.; Hebisch, R.; Brock, T.H.; Hartwig, A.; ,
Abstract: This analytical method is a validated measurement procedure for the determination and limit value monitoring of diethylene glycol, ethylene glycol and propylene glycol in workplace air. With this method simultaneously airborne glycols in the gaseous state as well as particles are collected. Sampling is performed by drawing a defined volume of air through the sampling system GGP‐Mini consisting of a glass fibre filter and a charcoal tube connected downstream using a suitable flow‐regulated pump. The flow rate is set to 0.33 L/min with a recommended air sample volume of 40 L. The collected glycols are desorbed with a mixture of dichloromethane/methanol containing 1‐hexanol as internal standard and then analysed by means of gas chromatography using FID. The quantitative evaluation is based on calibration functions obtained by means of multiple‐point calibrations. The limit of quantification (LOQ) for the individual glycols is 0.5 mg/m 3 based on an air sample volume of 40 L. Joint Publication of the Analytical Subcommittee of the Chemistry Board of Experts of the Expert Committee Raw Materials and Chemical Industry of the German Social Accident Insurance and the working group "Air Analyses" of the Permanent Senate Commission of the Deutsche Forschungsgemeinschaft for the Investigation of Health Hazards of Chemical Compounds in the Work Area.